2006
DOI: 10.3386/w12149
|View full text |Cite
|
Sign up to set email alerts
|

Household Finance

Abstract: The study of household finance is challenging because household behavior is difficult to measure, and households face constraints not captured by textbook models. Evidence on participation, diversification, and mortgage refinancing suggests that many households invest effectively, but a minority make significant mistakes. This minority appears to be poorer and less well educated than the majority of more successful investors. There is some evidence that households understand their own limitations and avoid fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
401
0
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(425 citation statements)
references
References 85 publications
17
401
0
7
Order By: Relevance
“…It is very possible that many borrowers fail to refinance even though it is optimal for them to do so, and previous work (for example, Campbell 2006) has found that this mistake seems more prevalent among borrowers with characteristics that correlate with low FICO scores. Indeed, such borrowers are sometimes called "woodheads" in the mortgage industry (Deng and Quigley 2006), precisely because they are slower to refinance.…”
Section: Open Questionsmentioning
confidence: 99%
“…It is very possible that many borrowers fail to refinance even though it is optimal for them to do so, and previous work (for example, Campbell 2006) has found that this mistake seems more prevalent among borrowers with characteristics that correlate with low FICO scores. Indeed, such borrowers are sometimes called "woodheads" in the mortgage industry (Deng and Quigley 2006), precisely because they are slower to refinance.…”
Section: Open Questionsmentioning
confidence: 99%
“…All statistics are as of December 2010. that offered by a non-interest bonus contract during the saving period, which comes at a cost of an approximately 1.3% higher credit interest rate. Although choosing the right contract is a complicated problem from a household perspective (Cocco, 2005;Campbell, 2006), we note that the mean contract volume is below 20,000 €, as shown in the empirical analysis. Consequently, customers must use other significant sources of funding to buy or refurbish real estate, and evaluating the importance of the credit option from a customer's perspective may not be critical.…”
Section: Introductionmentioning
confidence: 81%
“…Finally, the household finance literature considers the people's views and questions how they invest their capital (Campbell, 2006;Calvet et al, 2007;Bergstresser and Poterba, 2004). In contrast, our perspective takes the reverse approach; we take the bank's perspective and analyze how a bank can influence the behavior of its customers, regardless of what other investments they undertake.…”
Section: Related Literature and Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…For households, portfolio decisions should be seen in a life-cycle perspective incorporating human capital and real estate, the dominant assets for many households (Campbell 2006). The ability to predict house prices and labor income is potentially as important for households as stock market predictability.…”
Section: Introductionmentioning
confidence: 99%